PENGARUH DIVERSIFIKASI PRODUK DAN SOCIAL MEDIA PROMOTION TERHADAP MINAT BELI ULANG PADA UMKM NU JAKABA PLUS ARJASA SITUBONDO DIMODERASI OLEH KEPUASAN KONSUMEN - Afandi, Arif; Wahyuni, Ika; Rachman, Riza (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The purpose of this study is to determine the Effect of Product Diversification and Social Media Promotion on Repurchase Interest in UMKM NU Jakaba Plus Arjasa Situbondo Moderated by Consumer Satisfaction. The sampling technique used in this study was simple random sampling of 77 consumers. Data analysis and hypothesis testing in this study used the Structural Equation Model - Partial Least Square (PLS-SEM) The results of the study indicate that Product Diversification has a significant positive effect on Repurchase Interest, Social Media Promotion has a negative but significant effect on Repurchase Interest, Consumer satisfaction significantly moderates the effect of Product Diversification on Repurchase Interest, Consumer satisfaction significantly moderates the effect of Social Media Promotion on Repurchase Interest.